1999
DOI: 10.1093/emboj/18.9.2563
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the HMG protein NHP6A and its interaction with DNA reveals the structural determinants for non-sequence-specific binding

Abstract: NHP6A is a chromatin-associated protein fromSaccharomyces cerevisiae belonging to the HMG1/2 family of non-specific DNA binding proteins. NHP6A has only one HMG DNA binding domain and forms relatively stable complexes with DNA. We have determined the solution structure of NHP6A and constructed an NMR-based model structure of the DNA complex. The free NHP6A folds into an L-shaped three α-helix structure, and contains an unstructured 17 amino acid basic tail N-terminal to the HMG box. Intermolecular NOEs assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
227
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(240 citation statements)
references
References 68 publications
9
227
1
3
Order By: Relevance
“…Upon binding to DNA however, the N-terminus adopts structure, wrapping around the DNA (17). It has been shown that this N-terminal tail is indispensable for the stable interaction with DNA and for proper bending (17). A similar phenomenon has been demonstrated for the B-domain of HMG-1 (42).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Upon binding to DNA however, the N-terminus adopts structure, wrapping around the DNA (17). It has been shown that this N-terminal tail is indispensable for the stable interaction with DNA and for proper bending (17). A similar phenomenon has been demonstrated for the B-domain of HMG-1 (42).…”
Section: Discussionmentioning
confidence: 71%
“…When not bound to DNA, the acidic N-terminal tail is relatively unstructured. Upon binding to DNA however, the N-terminus adopts structure, wrapping around the DNA (17). It has been shown that this N-terminal tail is indispensable for the stable interaction with DNA and for proper bending (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that Nhp6 converts nucleosomes to an altered form in which the DNA is locally more accessible to DNase I or is a more suitable substrate for this nuclease and that unlike free nucleosomes this form is competent to bind Spt16-Pob3. DNA is dramatically bent by Nhp6 binding (27), and this could alter nucleosomes by disrupting local histone-DNA contacts. Nhp6 might bind to linker DNA and disturb contacts at the entry-exit points (linkers are defined here as the DNA extending beyond the 146-bp sea urchin 5 S rDNA nucleosome positioning sequence, Ref.…”
Section: Resultsmentioning
confidence: 99%